2003
DOI: 10.1038/sj.bjc.6600946
|View full text |Cite
|
Sign up to set email alerts
|

Are diet–prostate cancer associations mediated by the IGF axis? A cross-sectional analysis of diet, IGF-1 and IGFBP-3 in healthy middle-aged men

Abstract: We examined the association of diet with insulin-like growth factors (IGF) in 344 disease-free men. Raised levels of IGF-I and/or its molar ratio with IGFBP-3 were associated with higher intakes of milk, dairy products, calcium, carbohydrate and polyunsaturated fat; lower levels with high vegetable consumption, particularly tomatoes. These patterns support the possibility that IGFs may mediate some diet -cancer associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
97
6
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 26 publications
10
97
6
1
Order By: Relevance
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, no association between either tomatoes or lycopene and IGF-I or IGFBP-3 was observed. Four cross-sectional studies have investigated the relationship between tomato consumption [14,15,18] or lycopene intake [22] and IGF-I and IGFBP-3. In three of these studies, higher intake of cooked or processed tomatoes or lycopene was associated with either lower IGF-I levels [14], higher IGFBP-3 levels [22], or a lower IGF-I/IGFBP-3 molar ratio [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations